Phenological Characteristics and Environmental Factor Associations in Open-Field Cultivation of Pepino on the Qinghai-Tibet Plateau - Zhichao Hou; Cheng Si; Qiwen Zhong; Haiwang Zhang; Ziran Guo; Guangnan Zhang; Dengkui Shao; Shipeng Yang (International Journal of Fruit Science)
In the eastern Tibetan Plateau, the pepino plays a crucial role for environment. However, a challenge is the lack of a standardized system to track its growth stages, making it challenging to compare phenology in different areas. We investigated the growth stages of pepino using the Biologische Bundesanstalt, Bundessortenamt, and Chemical Industry (BBCH) scale as a reference framework. Our study delineated a comprehensive set of growth stages, covering nine primary stages from vegetative to reproductive, ending in complete senescence. Utilizing the BBCH growth stage scale, we documented and standardized the nutritional and reproductive growth stages of pepino at four distinct locations on the Qinghai-Tibet Plateau. We used linear regression analysis to compare agronomic traits of pepino across these regions, aiming to explore potential correlations between plant phenology and ecological factors. Results revealed that UV intensity and sunshine hours exerted the most significant influence on pepino’s phenological phases, emerging as crucial environmental factors. Evaporation and relative humidity also demonstrated notable impacts. Our findings highlight multi-year and multi-environmental associations between phenology and growth traits, suggesting that climatic differences may impose physiological constraints on the plant’s development. In summary, this study brings clarity to pepino’s growth and development stages, establishing a unified standard for its cultivation and breeding processes. The comprehensive insights gained have far-reaching implications for improving pepino cultivation practices and enhancing adaptability in diverse environmental conditions.